Pengaruh Employee Participation, Budaya Organisasi, dan Kedisiplinan Terhadap Produktivitas Kerja Pegawai - Simarmata, Sovianti; Sinurat, Elperida Juniarti; Saragih, Hendri (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine and analyse simultaneously the effect of employee participation, organisational culture, and discipline on employee work productivity at the Health Office UPTD Puskesmas Ndokum Siroga Village Simpang Empat District Karo Regency. This study uses a type of quantitative research. In this study the sample was all employees at the Health Office of the UPTD Puskesmas of Ndokum Siroga Village, Simpang Empat District, Karo Regency, totalling 31 people. Based on the results of the t hypothesis test, it can be concluded that partially employee participation has a significant effect on employee work productivity, partially organisational culture has a significant effect on employee work productivity, partially discipline has a significant effect on employee work productivity. Based on the results of the F hypothesis test, it can be concluded that simultaneously / together employee participation, organisational culture, and discipline have a significant effect on employee work productivity. Based on the results of the coefficient of determination analysis, the coefficient of determination or Adjusted R-Square value is 0.861 or 86.1%, which means that the effect of employee participation, organisational culture, and discipline on employee work productivity is 86.1%, while the remaining 13.9% is influenced by other variables or factors not examined in this study.